Analisis Pengukuran Produktivitas Dengan Menggunakan Metode Value Added Productivity Dan Productivity Ratio - Ririn Regiana Dwi Satya (Sosio e-Kons, 2014)
Asahimas Flat Glass Tbk PT is a leading producer of flat glass and automotive glass in Indonesia. Modern industry is in a highly competitive global market embracing the concept of production rather than as an activity to transform inputs into outputs. Currently, the production concept is seen as the creation of value-added activities (value added), for each activity in the process must add value. Understanding the added value perceived is very important, it is useful to avoid waste (waste) in any productive activity. Currently, the benchmark used to assess the performance of the company based solely on the amount of output produced. Increasing the amount of output does not necessarily mean the company is also increasing productivity. Based on this conceptual research to measure productivity using value added productivity and value added productivity ratio as a basis for planning for increased productivity. From the results of measurements that have been made of the obtained value of value added productivity for the year 2009 amounted to 1,337,494 (Million) and in 2010 amounted to 1,792,329 (Million). As well as can be determined the ratio of the productivity and value of the Economic Value Added in 2010 amounted to 264,813.16 (Million Euro). Productivity measurement results using the value added productivity then do the evaluation, planning and productivity improvement to improve productivity in the company.